ANTIBACTERIAL ACTIVITY OF A PIGMENT PRODUCING-BACTERIUM ASSOCIATD WITH Halimeda sp. FROM ELAND-LOCKED MARINE LAKE KAKABAN, INDONESIA - Ocky Karna Radjasa; Leenawaty Limantara; Agus Sabdono (JOURNAL OF COASTAL DEVELOPMENT, 2009)
A pigment producing-bacterium associated with green alga Halimeda sp., was successfully isolated from a land-locked marine lake Kakaban, East Borneo, Indonesia and screened for an antibacterial activity against pathogenic Staphylococcus aureus. The bacterium was identified as Pseudoalteromonas piscicida based on its 16S rDNA and was found to produce xanthophyll pigments and to amplify gene fragments of Non-ribosomal peptide synthetase (NRPS).